A case study on farm labour substitution in South Africa - Rossouw, Jannie (African Journal of Employee Relations, 2019)
This paper reports a case study on labour substitution by a small-scale farmer on his farm in the Western Cape Province of South Africa that has been owned by descendants of the same family since the early 1800s. Production techniques used on the farm have moved from labour-intensive to capital-intensive. The first step towards mechanisation was taken early in 1988, when some of the farm workers did not return after their annual holidays and before the harvesting season. One of the decisive reasons for the change in production techniques was a labour strike during the harvesting season in 2000. An analysis of gross income and production costs in 2012/13, based on capitalintensive production, compared to assumed costs if the labour-intensive production techniques of 1984/85 had been retained, shows an annual saving of R95 101 (19,5%) in comparative production costs. Moreover, capital-intensive production protects the farm against the danger of strikes and therefore reduces production risks considerably. This research raises questions about (i) the morality of capital-intensive production; (ii) the full cost of labour, compared to the full cost of capital, when the risks of unreliable labour and of labour strikes are taken into consideration; and (iii) the risk of land expropriation.